Identification of a novel PHGDH covalent inhibitor by chemical proteomics and phenotypic profiling - Chen Chen; Tianyu Zhu; Xiaoqin Liu; Dongrong Zhu; Yi Zhang; Sifang Wu; Chao Han; Hao Zhang; Jianguang Luo; Lingyi Kong (Elsevier, 2022)
The first rate-limiting enzyme of the serine synthesis pathway (SSP), phosphoglycerate dehydrogenase (PHGDH), is hyperactive in multiple tumors, which leads to the activation of SSP and promotes tumorigenesis. However, only a few inhibitors of PHGDH have been discovered to date, especially the covalent inhibitors of PHGDH. Here, we identified withangulatin A (WA), a natural small molecule, as a novel covalent inhibitor of PHGDH. Affinity-based protein profiling identified that WA could directly bind to PHGDH and inactivate the enzyme activity of PHGDH. Biolayer interferometry and LC-MS/MS analysis further demonstrated the selective covalent binding of WA to the cysteine 295 residue (Cys295) of PHGDH. With the covalent modification of Cys295, WA blocked the substrate-binding domain (SBD) of PHGDH and exerted an allosteric effect to induce PHGDH inactivation. Further studies revealed that with the inhibition of PHGDH mediated by WA, the glutathione synthesis was decreased and intracellular levels of reactive oxygen species (ROS) were elevated, leading to the inhibition of tumor proliferation. This study indicates WA as a novel PHGDH covalent inhibitor, which identifies Cys295 as a novel allosteric regulatory site of PHGDH and holds great potential in developing anti-tumor agents for targeting PHGDH.